Existence results for Schrödinger p(⋅)-Laplace equations involving critical growth in RN. (May 2019) - Ho, Ky; Kim, Yun-Ho; Sim, Inbo
Abstract: We establish some existence results for Schrödinger p ( ⋅ ) -Laplace equations in R N with various potentials and critical growth of nonlinearity that may occur on some nonempty set, although not necessarily the whole space R N . The proofs are mainly based on concentration-compactness principles in a suitable weighted variable exponent Sobolev space and its imbeddings.